“Happiness in the air?” the effects of air pollution on adolescent happiness - Wen-Hsu Lin; Wen-Chi Pan; Chin-Chun Yi (BMC Public Health, 2019)
Abstract Background We aimed to examine the effect of ambient air pollution at the district level on adolescents’ happiness and their change in happiness over time in a cohort sample from Taiwan. Method A cohort from the Taiwan Youth Project was evaluated. The adolescents (n = 2571) were in the 7th grade (mean age = 14.3 years) when the study was initiated and resided in 40 districts in three cities and counties in northern Taiwan. We examined the effects of the concentration level of air pollution, including PM2.5, PM10, and NO2, at the district level on adolescents’ happiness and their change in happiness over time (7th to 9th grade). Due to the high correlations of the three pollutants, we examined each separately with similar covariates. The analyses were based on both multilevel modeling and latent growth curve modeling. Results Higher concentration levels of each of the three air pollutants measured were associated with adolescent happiness such that a higher level of concentration was related to lower levels of adolescents’ happiness. These results were observed after controlling for important individual- and district-level covariates. However, further analyses did not reveal that the concentration level of air pollution was associated with the change in happiness in the study period (after 3 years). Some sensitivity checks (e.g., adjusting district size) did not change the substantive results. Conclusion Many previous studies have shown the influence of air pollution on physical health and negative emotions, but only a few using adult samples have shown that air pollution is inversely related to positive wellbeing. This study may be the first to examine the effects of air pollution on adolescents’ positive affect. Our results echo recent research on the consequent health burden of air pollution. Given that positive affect has been linked to future adult health, the results of the current study provide empirical grounds for early intervention concerning environmental factors.